Rome Statute of the International Criminal Court : a commentary - Triffterer, Otto; Ambos, Kai (München, Germany : Oxford, United Kingdom : Baden-Baden, Germany : Hart ; Nomos, 2016)
In the third edition of their much acclaimed commentary, Otto Triffterer, Kai Ambos and a number of eminent legal practitioners and scholars in the field of international criminal law give a detailed article-by-article analysis of the Statute, as well as the 'Elements of Crime' and the 'Rules of Procedure and Evidence' adopted by the Assembly of States Parties in 2002, and the 'Regulations of the Court'. The Second Edition was winner of the 2009 American Society of International Law Certificate of Merit for High Technical Craftsmanship and Utility to Practicing Lawyers and Scholars. Praise for the Second Edition 'Clearly written by experts in the field, skillfully edited, the commentary will prove indispensible to any serious scholar or practitioner of international criminal law.' German Yearbook of International Law ' ... indispensable for both academic international lawyers and practitioners, whether at public service or in private practice.' Alexander Orakhelashvili, European Journal of International Law.
Establishment of the court -- Jurisdiction, admissibility and applicable law -- General principles of criminal law -- Composition and administration of the court -- Investigation and prosecution -- The trial -- Penalties -- Appeal and revision -- International cooperation and judicial assistance -- Enforcement -- Assembly of states parties -- Financing -- Final clauses.
On the title page, the name Otto Triffterer is followed by a dagger.
Includes bibliographical references and index.
Keywords: International Criminal Court; International Criminal Court -- Rules and practice; International Criminal Court; Rome Statute of the International Criminal Court -- (1998 July 17); Rome Statute of the International Criminal Court (1998 July 17); International criminal courts -- Rules and practice; International crimes; 2; Juridictions internationales; 2; 2; 2; Crimes de guerre; Commentaires; International crimes; International criminal courts -- Rules and practice; Law commentaries; Rules; Law commentaries